2013
DOI: 10.5114/ninp.2013.36757
|View full text |Cite
|
Sign up to set email alerts
|

Markers of angiogenesis (CD31, CD34, rCBV) and their prognostic value in low-grade gliomas

Abstract: Density of microvessels as assessed immunohistochemically with CD31+ and CD34+ in LGG correlated with the value of rCBV in the tumour. The value of 1.75 for rCBV may be the threshold for better or poorer outcome of these patients. Expression of CD31 antigen is an important prognostic factor for the time of survival for patients with LGG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…To verify activation of the pro-angiogenic pathway in the recipient myocardium, we measured expression of CD31 by IHC. CD31, a marker for angiogenesis 36, 37 , was significantly overexpressed in the hCM- and iCM-treated myocardium (Figure 6B-C, E-F, p<0.05 vs. hESC/iPSC groups), confirming the effect of pro-angiogenic cytokines from hCM and iCM supernatant.…”
Section: Resultsmentioning
confidence: 54%
“…To verify activation of the pro-angiogenic pathway in the recipient myocardium, we measured expression of CD31 by IHC. CD31, a marker for angiogenesis 36, 37 , was significantly overexpressed in the hCM- and iCM-treated myocardium (Figure 6B-C, E-F, p<0.05 vs. hESC/iPSC groups), confirming the effect of pro-angiogenic cytokines from hCM and iCM supernatant.…”
Section: Resultsmentioning
confidence: 54%
“…Immunohistochemistry analysis shown an increase of CD34 + (microvascular density) in the patients. In the recent years, many studies have demonstrated that CD34 + blood vessels play a prominent part in tumour development and influence malignant severity . Tichet et al .…”
Section: Discussionmentioning
confidence: 99%
“…5 In recent years, studies have demonstrated that CD34-positive vessels play pivotal roles in the development of gliomas and have an influence on the malignant severity. 10,11,13 There have been a few reports that have comprehensively described the significance of CD34 in glioma patients and the specific roles of CD34 in the grading and prognosis of gliomas remain unclear. Therefore, it is unclear whether CD34 can be used as a marker of WHO grades in gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…This occurs by the increased supply of oxygen and other necessary metabolites, which leads to brain invasion and a worsened prognosis. 1012 …”
Section: Introductionmentioning
confidence: 99%